Serum Vitamin D Level and it’s Clinical Correlation with Rheumatological Diseases - Razzak, Md Abdur; Rahman, Md Anisur; Begum, Most Umme Habiba; Islam, Md Ifthakharul (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Vitamin D deficiency or insufficiency is a worldwide problem including Bangladesh. It is common in Rheumatological diseases. Objectives: To find outthe clinical correlation of serum Vitamin D level with Rheumatological diseases. Materials and Methods: This was a hospital based case control study. It was conducted in Rheumatology department of Combined Military Hospital Dhaka. Total 100 patients having Rheumatological diseases and 100 age and sex matched healthy control were included in the study. Data were collected from face to face interview, clinical examination and relevant investigation reports and processed with SPSS version 20 and obtained in tables and charts. Results: Among 100 study patients’Osteoarthritis (OA) were 24(24.0%), Rheumatoid arthritis (RA) 20(20.0%), SLE 16(16.0%), Osteoporosis 16(16.0%), Ankylosing spondylitis (AS) 10(10.0%), Chikungunya arthritis (CS) 4(4.0%)and other arthritis 10(10.0%). Among patients group 84(84.0%) had vitamin D deficiency/ insufficiency, of whom OA were 20(23.80%), RA 16(19.04%), SLE 16(19.04%), osteoporosis 14 (16.66%),AS 8(9.52%), CS 2(2.38%) and other arthritis 8(9.52%).Abnormal vitamin D level were in SLE 16(100.0%), osteoporosis 14(87.50%), OA20(83.33%), RA(80.0%), AS 8(80.0%), CS 2(50.0%), and other arthritis 8(80.0%).In study patients, 60 had adequate sun exposure of whom 48(72.07%) had low serum vitamin D level and 40 had inadequate sun exposure of whom 36 (90.0%) had low vitamin D level that reflects sunlight exposure affects vitamin D status.Abnormal serum vitamin D level was more common in Rheumatological diseased patients than healthy group (p <0.01). Conclusion: Abnormal vitamin D level were more in Rheumatological diseases than healthy control group that was statistically significant; it was also affected by lifestyle of patients. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 101-105